Ultimate rocket blast - Mian, Zanib (London: Hodder Children's Books, 2022)
Omar and his friends are taking part in a national rocket building competition. With a little help from Omar's scientist mum and dad and some fart power too, they come up with a rocket that's ready to blast off. But when someone starts sabotaging the rockets, the boys find themselves on a new mission: to reveal the culprit
Keywords: Children's stories